1985
DOI: 10.1073/pnas.82.8.2488
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cellular retinoid-binding proteins and transthyretin (prealbumin) are all localized in the islets of Langerhans in the rat.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…CRABPs may have some role in development of islets because they are localized in adult islets (31), and transgenic mice overexpressing CRABP I die prematurely as a result of tumor originating from islet of Langerhans (32).…”
Section: Discussionmentioning
confidence: 99%
“…CRABPs may have some role in development of islets because they are localized in adult islets (31), and transgenic mice overexpressing CRABP I die prematurely as a result of tumor originating from islet of Langerhans (32).…”
Section: Discussionmentioning
confidence: 99%
“…Islets were then thawed and homogenized in 1 ml of assay buffer containing 50 mM imidazole buffer pH 7.4,0.79% NaCl, 0.03% bovine serum albumin, 0.1I% thiomerosal, 0.0 1% leupeptin, and 1.0% Triton X-1I00. CRBP and CRABP levels were determined by recently developed sensitive and specific radioimmunoassays for each protein (7,20 Islet insulin and protein content. Islets were isolated from groups of normal, A-deficient, and retinoic acid-and retinyl palmitate-repleted rats.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies (7) have demonstrated the presence of relatively high levels ofCRBP, CRABP, TTR, and RBP in pancreatic rat islets. We have also shown that retinoids influence islet insulin secretion, ultrastructure and cell aggregation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…We explored this issue in our experimental crosses. The rationale was that, since the FoxO1 transgene is expressed from the transthyretin promoter, it should affect proliferation not only of terminally differentiated β cells but also of duct cells, a site of transthyretin expression (28). We obtained 2 surrogate measures of β cell "neogenesis" by counting β cell singlets/doublets and β cells abutting the lumen of pancreatic ducts (4,21,22).…”
Section: Early-onset Diabetes In Double-mutant Mice Transgenic Mice mentioning
confidence: 99%